Glass-based composites comprised of CaWO4:Yb3+, Tm3+ crystals and SrAl2O4:Eu2+, Dy3+ phosphors for green afterglow after NIR charging - Santos Magalhães E.; Sedda A.; Bondzior B.; Vuori S.; Van der Heggen D.; Smet P.F.; Lastusaari M.; Petit L. (Elsevier Ltd, 2025)
In this paper, we demonstrated the fabrication of new phosphate-based composites with green persistent luminescence after being charged with near-infrared light using the direct doping method. The composites are composed of a phosphate glass and phosphors. The 75NaPO3 − 25CaF2 and 90NaPO3 − 10NaF (in mol%) were the 2 glasses of investigation. The intense blue up-conversion emission between 450 and 500 nm upon 980 nm pumping is obtained by adding CaWO4: Tm3+, Yb3+ crystals in the glass melt before quenching whereas the green persistent luminescence is from the SrAl2O4:Eu2+,Dy3+ phosphors also added in the glass melt. The green persistent luminescence above 0.3 mcd/m2 is observed for ∼30 min after charging with 980 nm due to energy transfer between the upconverter crystals and the persistent luminescent phosphors. Here, the challenges related to the fabrication of such composites are discussed. While it is important for the blue UC emission to be intense to charge the SrAl2O4:Eu2+,Dy3+ crystals, we demonstrate that the glass matrix should not crystallize upon the addition of the different crystals. Additionally, the composites should remain translucent with limited light scattering for the blue UC emission to charge the persistent luminescent phosphors.